Austin American-Statesman Omar L. Gallaga column - Gallaga, Omar L (TCA Regional News, 2015)
A light bulb idea moment My remote only works with a limited number of home automation product lines, and one of those was Philips Hue, a line of smart lights I'd heard about and dismissed long ago as too expensive and impractical. The TV network Syfy announced that its new TV show "12 Monkeys" would sync to Hue lights, allowing audio cues from the series to change the color and intensity of lights in the room.\n